The Implementation of Range of Motion Exercises in Overcoming Impaired Physical Mobility in Rheumatoid Arthritis - Zuraidah; Nadi Aprilyadi; Intan Kumalasari; Tri Agus Wahyudianto; Wella Juartika (Formosa Journal of Science and Technology, 2023)
Rheumatoid arthritis (RA) is a disease characterized by an autoimmune chronic inflammatory disorder or autoimmune response that causes weakening of the joints and lining of the synovial organs, especially in the hands, feet, and knees. This study aims to determine the implementation of nursing care with active and passive motion exercises for impaired physical mobility in patients with rheumatoid arthritis in the work area at Taba Health Center, Lubuklinggau City, in 2022. The method used is descriptive in the form of a case study with two clients experiencing rheumatoid disease as subjects. arthritis with impaired physical mobility problems that experience joint stiffness. The results showed that after being given active and passive motion training therapy, muscle strength increased. Implementation of nursing care with active and passive motion exercises can increase muscle strength in clients with rheumatoid arthritis. Because this motion exercise does not require costs and each movement can be done independently at home.